Interrogating the Legal Foundations of Digital Transformation: Balancing Economic Growth and Social Welfare in the Era of Disruption - Anggono, Bayu Dwi; Wahanisa, Rofi; Sari A.P, Aulia Oktarizka Vivi Puspita; Adiyatma, Septhian Eka (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
Digital transformation has emerged as a crucial component of Indonesia’s national development strategy, recognized for its capacity to stimulate economic growth, enhance public services, and improve social welfare. However, the current approach tends to be technocratic, often overlooking vital legal, institutional, and justice-related issues. This study critically assesses examine the adequacy and coherence of Indonesia’s legal and institutional frameworks governing digital transformation to promote inclusive economic growth and social welfare. It identifies regulatory and institutional gaps and recommends strategic reforms for equitable digital governance. Employing a socio-legal methodology that merges doctrinal legal analysis with interdisciplinary insights from political science, economics, and sociology, this research evaluates key legal instruments and institutional practices, alongside global best practices, to determine Indonesia’s readiness for digital transformation. The findings indicate that Indonesia’s progress is hampered by fragmented and reactive legal frameworks, notable regulatory gaps—particularly in data protection and labor rights within the gig economy—and weak institutional coordination. These issues lead to policy inconsistencies, implementation delays, and the exacerbation of existing inequalities. To address these challenges, this study advocates for a systemic reconfiguration of digital governance grounded in democratic principles and inclusive participation. It proposes six strategic pillars: infrastructure, digital human capital, business climate and cybersecurity, research and innovation, funding and investment, and robust legal-regulatory frameworks, to ensure a just and sustainable digital transition.